Determination of the flow curve of necking tensile specimen - Razali, Nadlene (2010)
The main objective of this project is to study and to determine the flow curve of necking specimen by using finite element analysis and to validate the approximation formulae of equivalent plastic stress and strain introduced by Bridgman and Davindekov-Spiridonova. This research is done for 3 tensile test specimens with different types of hardening which are ideal plasticity, linear hardening and non linear hardening. In this project, the finite element method is applied for high accurate simulation of tensile tests. The obtained results are discussed in the context of approximation formula and previously known results. Different numbers of element have been carried out in order to study the influence of meshing on the results. From the study, it was found that larger number of elements give stable results, thus, larger number of elements are been choose for simulation. Computer simulation has been done to verify the assumption of the approximation formula and to recognize the possible error. From the results interpretation, it was stated that the error connected with application of the simple formula can be estimated as 10 % in comparison with the numerical simulations, which was considered as the reference solution. The results shows that, the Davidenkov Spiridonova approximation formula give better compared to the Bridgman formula.